2016
DOI: 10.5194/amt-2016-152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of IWV from the numerical weather prediction WRF model with PPP GNSS processing for Bulgaria

Abstract: Abstract. Global Navigation Satellite Systems (GNSS) meteorology is an established operational service providing hourly updated GNSS tropospheric products to the National Meteorologic Services (NMS) in Europe. In the last decade through the ground-based GNSS network densification and new processing strategies like Precise Point Positioning (PPP) it has become possible to obtain sub-hourly tropospheric products for monitoring severe weather events. In this work one year (JanuaryDecember 2013) of sub-hourly GNSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…This implies that pressure decreases with increasing altitude and vice versa, hence the possible reason the two are the potential cause of multicollinearity. Mathematically, pressure and altitude are related as follows (Liu et al, 2019;Simeonov et al, 2016;Sissenwine et al, 1962;Xu et al, 2020):…”
Section: Detection Of Multicollinearitymentioning
confidence: 99%
“…This implies that pressure decreases with increasing altitude and vice versa, hence the possible reason the two are the potential cause of multicollinearity. Mathematically, pressure and altitude are related as follows (Liu et al, 2019;Simeonov et al, 2016;Sissenwine et al, 1962;Xu et al, 2020):…”
Section: Detection Of Multicollinearitymentioning
confidence: 99%
“…It has the potential to forecast severe weather phenomena [2][3][4] and examine the effects of climate change [5,6]. Previous studies [3,[7][8][9][10] have shown that there will be severe rainstorms in the downward trend process after GNSS-PWV reaches its peak value. Benevides et al [11] proposed that the accuracy of weather forecasting could be improved after analyzing 3D distribution variations of PWV [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Being a key element of the hydrological cycle, it has a relatively short presence in the atmosphere, between less than a day and more than 30 days (van der Ent and Tuinenburg, 2017;Hodnebrog et al, 2019). Its complex life-cycle includes vertical and horizontal transport, mixing, condensation, precipitation and evaporation (Simeonov et al, 2016). Moreover, tropospheric water vapor increases in close association with global warming, and this represents a major climate feedback that shapes the global circulation of the atmosphere (Schneider et al, 2010;Solomon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%